All‐Solution Processed Multicolor Patterning Technique of Perovskite Nanocrystal for Color Pixel Array and Flexible Optoelectronic Devices. Issue 17 (25th May 2020) - Jeon, Sanghyun; Lee, Sang Yeop; Kim, Su‐Kyung; Kim, Woosik; Park, Taesung; Bang, Junsung; Ahn, Junhyuk; Woo, Ho Kun; Chae, Ji‐Yeon; Paik, Taejong; Seong, Tae‐Yeon; Oh, Soong Ju
Abstract: In the present study, a new patterning method is introduced through the surface modification and stabilization of perovskite nanocrystals, which is compatible with conventional photolithography process based on all‐solution processes. Chemically designed gel‐type silica‐coated CsPbX3 (X = Br, I, etc.) perovskite nanocrystals combined with dip coating method are introduced to form stable and uniform films. Analyses of the physical and chemical states of nanocrystals and investigation of the kinetics in silica formation are conducted. In an optimized condition, physically uniform and chemically stable perovskite thin films are deposited on various substrates such as flexible, stretchable substrates, or even nonflat objects. By adopting these advantages and developing stable photolithographic chemicals, the high resolution patterns are successfully patterned with green and red emitting CsPbBr3 and CsPbBr3 I3− x perovskites with the size down to 5 µm of radius and even a multicolor pixel array which can be used for the color filter, light converting or detecting applications. Flexible white light emitting diode is also fabricated with a large color gamut coverage. This work provides a fundamental understanding of perovskite nanocrystals, and also offers a technological breakthrough enabling various optoelectronic applications. Abstract : Silica‐coated all inorganic lead halide perovskite nanocrystals are successfully patterned using conventional photolithography with all‐solution processes. The perovskite could be patterned up to 5 µm of radius using this technique. Multicolor patterning is likewise achieved. Flexible white light emitting diode is fabricated. To achieve this, gel‐type silica‐coated perovskite, dip‐coating, surface chemistry, and solvent engineering are systematically investigated and modulated.